2005
DOI: 10.1111/j.1523-1755.2005.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor (HGF) modulates matrix turnover in human glomeruli

Abstract: HGF reduced expression and synthesis of TGF-beta and collagen type IV and increased MMP-2 mRNA level in normal human glomeruli. These results suggest an antifibrotic effect of HGF on glomerular cells and may explain its beneficial role in glomerulosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Previous studies indicated that TGF-β1 and HGF are counteracting in their biological activities (Mizuno et al, 2001). TGF-β1 strongly stimulates the synthesis of ECM proteins and inhibits the degradation of ECM (Esposito et al, 2005;. In contrast, HGF accelerates the degradation of ECM by modulating proteinases involved in the breakdown of ECM proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that TGF-β1 and HGF are counteracting in their biological activities (Mizuno et al, 2001). TGF-β1 strongly stimulates the synthesis of ECM proteins and inhibits the degradation of ECM (Esposito et al, 2005;. In contrast, HGF accelerates the degradation of ECM by modulating proteinases involved in the breakdown of ECM proteins.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports from experimental studies showing the protective effect of HGF against acute and chronic kidney injury [25-27]. Esposito and co-workers demonstrated that HGF reduced, in in vitro conditions, the expression and synthesis of TGF-beta and collagen type IV in normal human glomeruli [28]. There are also clinical observations suggesting an HGF stimulating effect in recovery of renal function in patients with acute renal failure [15].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of metalloproteases was revealed as white bands on the blue-stained gel. The intensity of the bands was measured using an image analyzer as previously reported [15] and results were expressed as the I/R kidney/control kidney ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Membranes were then incubated for 24 h at 4°C with anti-TGF-β antibodies (1:1,000; Santa Cruz Biotechnology, Santa Cruz, Calif., USA) and, after extensive washing, with horseradish peroxidase-conjugated secondary antibodies (1:10,000) for 1 h at room temperature in blocking buffer containing 5% milk. The signals were visualized using enhanced chemiluminescence system and quantified with an image analyzer [15]. β-Actin was used as control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation